2000
DOI: 10.1128/jb.182.24.6999-7006.2000
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of the Effect of Mucoid Conversion on Global Protein Expression in Pseudomonas aeruginosa Strain PAO1 Shows Induction of the Disulfide Bond Isomerase, DsbA

Abstract: Pseudomonas aeruginosa strains that cause chronic pulmonary infections in cystic fibrosis patients typically undergo mucoid conversion. The mucoid phenotype indicates alginate overproduction and is often due to defects in MucA, an antisigma factor that controls the activity of sigma-22 (AlgT [also called AlgU]), which is required for the activation of genes for alginate biosynthesis. In this study we hypothesized that mucoid conversion may be part of a larger response that activates genes other than those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
57
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 40 publications
(68 reference statements)
4
57
0
Order By: Relevance
“…Previously this protein has been shown to be more abundant in the mucoid mucA22 derivative versus wildtype PAO1 (Malhotra et al, 2000), which agrees with our data for planktonic cells. The expression of dsbA is under s-22 control, which is required for the activation of alginate biosynthesis genes.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Previously this protein has been shown to be more abundant in the mucoid mucA22 derivative versus wildtype PAO1 (Malhotra et al, 2000), which agrees with our data for planktonic cells. The expression of dsbA is under s-22 control, which is required for the activation of alginate biosynthesis genes.…”
supporting
confidence: 83%
“…The expression of dsbA is under s-22 control, which is required for the activation of alginate biosynthesis genes. A deletion of dsbA in PAO1 resulted in reduced twitching motility and reduced accumulation of extracellular proteases, including elastase (Malhotra et al, 2000), previously demonstrated to be present in the matrix material of FRD1 biofilms (Sarkisova et al, 2005).…”
mentioning
confidence: 99%
“…AceA and -B are subunits of pyruvate dehydrogenase, suggesting that metabolic imbalance influences the expression of T3SS (6,36). DsbA is a periplasmic thiol-disulfide oxidoreductase and was shown to affect T3SS expression, twitching motility, and intracellular survival of P. aeruginosa upon infection of HeLa cells (14,28). Interestingly, the dsbA gene is up regulated in the mucA mutant background, and its expression was shown to be affected by AlgU (28).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation in the mucA gene leads to derepression of AlgU, which in turn activates genes for alginate synthesis as well as others, such as dsbA, oprF, osmE, and rpoH (10,28). In the mucA mutant, not only the sigma factor AlgU but also AlgQ, an anti-70 factor, are activated (9), thus posing the possibility that sigma factor competition by AlgU and AlgQ effectively decreases the availability of 70 -containing RNA polymerase for the expression of T3SS genes (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation